Dynamic positioning for engineers - Kumar, Surender (Boca Raton : CRC Press, 2021)
Dynamic Positioning for Engineers enables the reader to acquire the basic knowledge of the concepts and understanding of the dynamic positioning (DP) system from the systems perspective. This book illustrates the system, subsystems and components of the DP system to better tackle maintenance, problems and breakdowns, leading to an increased mean time between failures and effective fault finding on dynamic positioning DP-related equipment. Overall, this text will help professionals reduce downtime and higher repair costs. Aimed at onboard electrical engineers, engine room watch officers, chief engineers, DP professionals onboard, in onshore officers and those taking DP training courses, this book: Explains automation and its application in the DP system Describes environmental sensors and position reference sensors as important inputs to the DP system Includes chapters on power management and thrusters Aids engineers in maintaining a the DP system in good operational condition
OCLC-licensed vendor bibliographic record.
Keywords: Ships -- Dynamic positioning systems; TECHNOLOGY / Electricity; TECHNOLOGY / Engineering / Civil